Development of wafer bonding technology for micro-electro-mechanical systems application - Wang, Lei. (2008)
Anodic wafer bonding technology is an important process for fabrication and packaging of Micro-Electro-Mechanical Systems (MEMS). This study concentrates on the anodic bonding process at lower t emperatures, which is more desirable for MEMS fabrication. A model of the electrostatic force was developed to investigate the relationships of the force and process parameters. The electrostatic force established during bonding becomes critical when the temperature variation is restricted. Modeling analysis showed that the magnitude of the electrostatic force was dependent on temperature and voltage, and the topology of the wafer surface does not significantly change its magnitude.